Optimization of dross formation rate in plasma arc cutting process by response surface method. (2020) - Sharma, Devaki Nandan; Kumar, J. Ram
Abstract: Plasma arc cutting (PAC) is widely used industrial process because of its high productivity and the ability to cut practically all materials. Dross formation is the major problem in PAC during cutting. It depends on various parameters i.e. current, Arc voltage, speed etc. In this investigation, the effect of cutting parameters on Dross formation rate (DFR) was studied. Safe Cutting Zone for PAC of Metal was determined first to find out the working range of process parameters. The experimental trials were designed by Response surface method. L30 orthogonal array was used. The mathematical model and optimum solution to minimize the DFR was made. A significant reduction was found in dross formation by the application of optimum solution obtained.